The impact of context cues on college students’ purchase behavior for low-carbon products in CBEC - Wang, Chen; Zhou, Xiaolong; Zhang, Ran; Liu, Yexin (Frontiers in Psychology, 2023)
Introduction The purpose of this study was to examine the effects of online shopping context cues (price discount, carbon label, and social commentary) on college students’ trust/perceived risk and cross-border purchase intention (CBPI) for low-carbon products and compare the study between South Korean and Chinese college students. The theoretical framework is established by integrating the S-O-R model and valence framework. The variable of stimuli (S) is the driving force in the purchase behavior that influences the individual organism (O) and its subsequent response (R). Based on this logic, this study draws on the valence framework to hypothesize the effects of online shopping context cues (price discount, carbon label, and social commentary) on college students’ trust/perceived risk and cross-border purchase intention (CBPI) for low-carbon products. Methods This study conducted two online experiment-questionnaire studies and one between-subject lab experiment to test the hypotheses. Results We found that all three context cues have significant positive effects on trust and negative effects on perceived risk. College students’ trust positively and perceived risk negatively impact college students’ CBPI for low-carbon products. In addition, based on different cultures, languages, and education, this study investigates the moderating effect of college students’ nationality on their significantly different cue processing modes for low-carbon products. Discussion The findings provide new insights into better understanding the factors affecting college students’ low-carbon consumption behavior in a CBEC setting and have some practical implications.